Effect of acupuncture on menopausal depressive disorder and serum hormone levels: a systematic review and meta-analysis - He, Shunxia; Wang, Zhijie; Dong, Shiqiu; Diao, Yuzi; Qiao, Hongwei; Lin, Xiaoguang; Gao, Xiao (Frontiers in Psychiatry, 2025)
BackgroundMenopause, marked by ovarian decline and hormonal shifts, increases vulnerability to depressive disorders, with menopausal depressive disorder (MDD) affecting 33–36% of women via psychosocial-biological interactions. Acupuncture shows promise in improving MDD through neuroendocrine regulation but lacks robust evidence, with unclear links to reproductive hormone modulation; this study evaluates its efficacy and safety.MethodsA comprehensive database search was conducted using PubMed, Embase, the Cochrane Library, Web of Science, EBSCO, Scopus, Cnki, Wan Fang and VIP Database to identify randomized controlled trials (RCTs) investigating the impact of acupuncture on menopausal depressive disorder. RCTs published until April 21, 2025, that met our predetermined inclusion and exclusion criteria were included. Data extraction, literature review, and assessment of the methodological quality of the trials were performed. The meta-analysis was conducted using Review Manager (RevMan) 5.3 software.ResultsOur findings demonstrate that acupuncture significantly outperforms control interventions in improving clinical effectiveness rates (OR=2.70, 95%CI[1.63,4.48], P=0.0001) and reducing depressive symptoms, as evidenced by HAMD-17 (SMD=-0.28, P<0.0001) and HAMD-24 scores (post-sensitivity SMD=-0.39, P=0.03). Notably, acupuncture also enhanced quality of life (MENQOL: SMD=-0.25, P=0.003), though its effects on sex hormones (FSH, LH, E2) remained nonsignificant (P>0.05). Safety profiles were comparable between groups (OR=0.16, P=0.05), yet sensitivity analysis revealed reduced adverse events in the acupuncture group after excluding outlier studies (OR=0.49, P=0.03). In conclusion, the intervention of acupuncture is beneficial for MDD.ConclusionThis systematic review demonstrates that acupuncture serves as an effective and safe non-pharmacological intervention for alleviating menopausal depressive symptoms and improving quality of life. While acupuncture did not significantly modulate sex hormone levels, its therapeutic benefits are likely mediated through non-hormonal mechanisms, such as neurotransmitter regulation and neuroendocrine network modulation.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251037010.